Financial Analysis of Broiler Farm Business in Batu Penjamuran Village Sub District Namorambe (Case Studies on farms Andarias with partnership patterns) - A L Ginting; E Mirwandhono; A H Daulay; Hasnudi; Sayed Umar (Talenta Publisher, 2018)
This research was conducted Batu Penjamuran Village Namorambe sub district. The research was conducted in June until December 2016. Research method used was case study at broiler farm Andarias. The location determination in this study was conducted directly on the basis that livestock farming Andarias was a potential farm and has had never been analyzed its business feasibility. This research was used data collection method by observation and direct interview to farmer Andarias. This research showed the income earned by breeder Andarias, in the year 2014 to 2016 sequantially each month as much as Rp. 9.327.568, Rp. 5.508.219, and Rp. 9.023.066.NPV value of 250,784,644, IRR of 66.58% and R / C of 1.08% which could then be declared as a reasonable information. Therefore, the conclusions generated by the researcher was a livestock business by Mr. Andarias expressed could be continued and developed.